Integrated bioinformatic changes and analysis of retina with time in diabetic rats - Cui, Zekai; Zeng, Qiaolang; Guo, Yonglong; Liu, Shiwei; Chen, Jiansu (PeerJ, 2018)
Diabetic retinopathy (DR) is the most common chronic complication of diabetes. It can cause impaired vision and even blindness. However, the pathological mechanism of DR is still unknown. In the present study, we use bioinformatic analysis to reveal the pathological changes of early DR in a streptozotocin (STZ) induced diabetes rat model. The dataset GSE28831 was downloaded from the Gene Expression Omnibus (GEO) database. To clarify the pathological mechanism of early DR, genes which were up-regulated (UP group) or down-regulated (DOWN group) over time were identified. One hundred eighty six genes in the UP group and 85 genes in the DOWN group were defined. There were in total 28 Gene ontology (GO) terms with a P value lower than 0.05 in UP group, including astrocyte development, neutrophil chemotaxis, neutrophil aggregation, mesenchymal cell proliferation and so on. In the DOWN group, there were totally 14 GO terms with a P value lower than 0.05, including visual perception, lens development in camera-type eye, camera-type eye development, bicellular tight junction and so on. Signaling pathways were analyzed with all genes in the UP and DOWN groups, and leukocyte transendothelial migration and tight junction were selected. Protein–protein interaction (PPI) network was constructed and six hub genes Diras3, Actn1, Tssk6, Cnot6l, Tek and Fgf4 were selected with connection degree ≥5. S100a8, S100a9 and Tek may be potential targets for DR diagnosis and treatment. This study provides the basis for the diagnosis and treatment of DR in the future.
Keywords: Differentially expressed genes; Gene ontology terms; Protein–protein interaction; Diabetic retinopathy; Bioinformatics